Translating Human Rights in Education: The Influence of Article 24 UN CRPD in Nigeria and Germany - Agbonlahor, Osasohan (Journal of International Students, 2023)
Both low-income and high-income countries have historically marginalized disabled children and youths. Inclusive education has been championed as a means to remove educational barriers, eliminate discrimination, and improve the outcomes of disabled persons. The book “Translating Human Rights in Education: The Influence of Article 24 UN CRPD in Nigeria and Germany” makes an important contribution to the field of inclusive education by examining two countries with very different educational systems, levels of economic development, and historical context. This book provides a nuanced analysis of the translation of human rights principles into practical educational policies and practices within these two diverse national contexts.